Association Between Dominant Wheat Stem Rust Races Found in Ethiopia and Grain Yield in Advance Bread Wheat Genotypes - Solomon, Tafesse; Sime, Berhanu; Dabi, Alemu; Alemu, Gadisa; Geleta, Negash; Negash, Tamirat; Delesa, Abebe; Zegeye, Habteamriam; Duga, Rut; Yirga, Fikrte; et al. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted in 2019 and in 2020 across two locations: Dhera and Asasa in Ethiopia to study the correlation between dominant stem rust races found in Ethiopia and grain yield on bread wheat genotypes found in the national wheat research program pipelines. Twenty three bread wheat genotypes and two released bread wheat varieties set as a Bread Wheat National Variety Trial by the national wheat research program for low altitude and planted at Dhera and Asasa. A square lattice design with two replications used for experiment conducted on the field. A plot of six rows, size of 2.5 m by 1.2 m, and a total area of 3 m2 used. The same genotypes planted using complete randomized design in three replications at Kulumsa Agricultural Research Center green house. Seven-day old seedlings were inoculated with spores of selected races: TTTTF, TKTTF, TKKTF, TTRTF and BULK. Data on infection types (IT) were recorded 14 days after inoculation using 0–4 scale. Result in the study revealed that Grain yield had positive genotypic association with all four races but bulk at Dhera. A very high negative significant genotypic correlation r=-0.708*** obtained between Grain yield and field Stem rust diseases score at Asasa. Those genotypes carrying race-specific effective gens for the races used in the green house were resistance at the seedling stage. But, on the field, at the adult stage, they lost the resistance and become susceptible.